• تقاطع اللسانيات التداولية والدرس اللغوي العربي القديم • The Intersection Of Pragmatic Linguistics And The Ancient Arabic Language Lesson - عبد الحكيم, سحالية (جامعة الوادي - University of Eloued, 2023)
ملخص: التداولية امتداد للبلاغة القديمة ، بل تعتبر حاملة محتوى تداوليا لاهتمامها بالباث والمستقبل والسياق والمقام،وتعود ملامح التداولية في الفكر العربي إلى كوكبة من العلماء كسيبويه ، الجاحظ، ابن جني ، أبي هلال العسكري ،ابن سنان الخفاجي، عبد القاهر الجرجاني، حازم القرطاجني، وغيرهم، لكن الفارق أن البلاغة العربية قديما تحمل الطابع المعياري، فهي تهتم بالأثر الناتج مباشرة عن الرسالة، والشروط التي تجعل الخطاب ناجحاً، وهي تشترك مع التداولية في كثير من المناحي والقضايا ،فقد ركز هؤلاء المنظرون على المرسل والمتلقي، والرسالة، وعملية التأثير والتأثر، والإقناع والقصد، والفائدة من الكلام، والإفهام،والبيان، وذلك وجه الاتفاق بينهما الكلمات المفتاحية: تقاطع_ اللسانيات_ التداولية_ الدرس _ اللغوي _ العربي_ Abstact Pragmatics is an extension of ancient rhetoric. Rather, it is considered a carrier of pragmatic content for its interest in the transmitter, and receiver, the context and the station. The features of pragmatics in Arab thought go back to a constellation of scholars like Sibawayh, Al-Jahiz, Ibn Jinni, Abi Hilal Al-Askari, Ibn Sinan Al-Khafaji, Abdul Qaher Al-Jurjani, Hazem Al-Qartagni, and others. But the difference is that the ancient Arabic rhetoric bears a normative character, as it is concerned with the effect resulting directly from the message, and the conditions that make the speech successful, and it shares with pragmatics in many aspects and issues. And the benefit from speaking, understanding, and clarifying, and that is the point of agreement between them • key words: intersection _ pragmatic _linguistics _ancient _Arabic_ language_ lesson
مقال
Keywords: تقاطع ; اللسانيات ; التداولية ; الدرس ; اللغوي ; العربي; intersection ; pragmatic ; linguistics ; ancient ; Arabic ; language ; lesson